Reputation management in global financial institutions - (:unkn) unknown (Springer International Publishing, 2014)
The economic crisis which began in the USA at the end of 2008 has first and foremost affected global financial institutions. The most destructive effect of the crisis on global financial institutions has been loss of reputation. It is obvious that large scale factors such as disruptions in current financial structures, the fragile structure of global financial architecture, assessments of risk system, and requirements for new regulations have impact on reputation and its management. However, from the managerial disciplinal point of view, reputation management is a comprehensive approach which involves the anticipation of all variables available, and where different stakeholders and circumstances are taken into consideration. The reputation of global financial institutions depends, in the final analysis, on the administrative processes of these institutions; in other words whether or not they are managed well. A good management requires foreseeing crises, and considering the opportunities and threats together with their strengths and weaknesses, and putting into practice an action plan towards that end together with the active participation of all their stakeholders. © Springer International Publishing Switzerland 2014. All rights are reserved.
Keywords: Reputation; Reputation management; Reputation management and Financial institutions